CT arthrography for evaluation of autologous chondrocyte and chondral-inductor scaffold implantation in the osteochondral lesions of the talus - De Filippo, Massimo; Azzali, Emanuele; Pesce, Antonella; Saba, Luca; Mostardi, Maurizio; Borgia, Daniele; Barile, Antonio; Capasso, Raffaella; De Palmi, Fabio; Caravaggio, Francesco (Acta Biomedica Atenei Parmensis, 2016)
Purpose: to analyse the findings of CT arthrography of the ankle, one year after the transplant of autologous chondrocytes in solution (ACI technique) and the covering with the only scaffold implantation of the osteochondral lesions of the talus, in comparison with the clinical evaluation of the ankle. Methods: This retrospective study includes 10 patients (6 male, 4 female, mean age 49.4, range 25-74 years) with an osteochondral lesion of the medial side of the talus, 4 pure chondrals, 6 osteochondrals, painful and limiting the articulation, who underwent ACI using autologous chondrocyte (5 cases) and a covering with the only scaffold implantation (5 cases), in patients who underwent multi-detector CT arthrography between April 2006 and December 2013, at least 12 months after the surgery. Results: Grade 0 was presented in 5 cases (50%), grade 1 in 2 cases (20%), grade 3 in 2 cases (20%) and grade 4 in 1 case (10%). Among the 5 cases even to 0 according to ICRS classification, the patient presented no symptoms in 4 out of 5 cases (80%); in 1 case, the patient presented post-operation pain of moderate entity due to the onset of adhesive capsulitis (20%). The 2 grade 1 patients, according to the ICRS classification, did not report any post-operation pain (0%). The 2 grade 3 patients, according to the ICRS classification, reported a light pain in 1 case (50%). The grade 4 patient, according to the ICRS classification, reported moderate pain (100%). Conclusions: The CT arthrography, for the elevate spatial and contrast resolution, is a very accurate exam in detecting irregularities in the chondral-inductor scaffold implantation, and in correlating the clinical presentation.